Microstructure and Property of Sintered Fe-2Cu-0.8C-0.6Mo-2W Materials Prepared From Prediffused Powders - Chen, Wenchao; Wang, Jinghui; Chen, Pengqi; Cheng, Jigui (Frontiers in Materials, 2020)
Prediffused Fe-W powder with 2 wt.% of tungsten was prepared by heating Fe-W powder mixes at 800 ℃ for 45 min in H2 atmosphere. Two kinds of Fe-2Cu-0.8C-0.6Mo-2W powder mixtures were obtained by mechanically mixing the prediffused Fe-W powders with the other elemental powders. After pressing and sintering, sintered Fe-2Cu-0.8C-0.6Mo-2W materials were obtained from the two powder mixtures. Effect of the introducing ways of tungsten element and sintering conditions on microstructure, mechanical and wear properties of the sintered samples were investigated. The results show that with the increase of sintering temperature and time, hardness and strength of sintered samples increase. Prediffused treatment of Fe-W powder can improve density of green compacts and sintered samples. When W element introduced in the form of prediffused Fe-W powders, the compacts pressed at 700 MPa have a green density of 7.13 g/cm3, and after sintered at 1150 ℃, the density, hardness, tensile strength and radial crushing strength of the sintered samples are 7.16 g/cm3, 95 HRB, 547 MPa and 791 MPa, respectively, which are higher than those of the samples prepared from powder mixtures by mechanically mixing the elemental powders. Furthermore, the prediffused treatment of Fe-W powders can improve the distribution of W element and enhance wear resistance.